Harmonizing faith and markets: The role of halal certification in Islamic economics - Mohd Hussin, Mohd Yahya; Muhammad , Fidlizan; Abdul Razak, Azila; Mahjom, Nurhanie (Journal of Islamic, Social, Economics and Development, 2025)
This mini review examines the role of halal certification in Islamic economics, highlighting its importance as both a religious safeguard ensuring Shariah compliance and an economic tool that enhances consumer trust, supports SMEs, and promotes global trade. A structured literature search was conducted in the Scopus database using keywords related to halal certification and Islamic economics, with inclusion limited to peer-reviewed studies published in English and exclusion of grey literature to ensure reliability. The review identifies four key thematic areas. First, global standards remain fragmented, with inconsistent criteria, auditing processes, and enforcement mechanisms creating inefficiencies and undermining consumer confidence, though initiatives such as Malaysia’s JAKIM and OIC-SMIIC provide partial frameworks. Second, consumer trust is reinforced by certification logos as markers of authenticity, yet fraudulent practices, weak oversight, and unrecognized certifying bodies erode confidence, raising debates over whether certification should expand beyond religious authenticity to include sustainability and ethical dimensions. Third, regulatory frameworks vary widely: centralized models offer credibility but face bureaucratic inefficiencies, while decentralized models provide flexibility but risk inconsistency and fraud, highlighting the need for hybrid approaches. Finally, the economic impact of halal certification is significant, contributing to GDP growth, brand competitiveness, and SME development, though high compliance costs and sectoral concentration limit inclusivity. Despite its potential, knowledge gaps persist in understanding demographic-specific consumer behaviour, cross-sectoral applications, and long-term economic outcomes. Future research should prioritize harmonized standards, cost-effective SME models, and technological integration, particularly blockchain and digital traceability, to enhance transparency, build trust, and position halal certification as a driver of sustainable and ethical global economic growth.